Possible functions of ecdysone signaling reiteratively used in the adult honey bee brain - Matsumura, Yasuhiro; Kohno, Hiroki; Kubo, Takeo (Frontiers in Bee Science, 2023)
The European honey bee is a model organism for investigating the molecular and neural bases of the brain underlying social behaviors. Mushroom bodies (MBs) are a higher-order center of memory, learning, and sensory integration in insect brains, and honey bee MBs are a model to study adult neuronal plasticity. In the honey bee, MBs comprise three Class I Kenyon cell (KC) subtypes: large-, middle-, and small-type KCs, which are distinguished based on the size and localization of their somata, and gene expression profiles. One of the unique characteristics of honey bee MBs is that genes for ecdysone signaling are expressed in a spatially and temporarily regulated manner in the adult brain, suggesting that they play a role in the functional specialization of each KC subtype and behavioral control. A recent study reported that the transcription factor Mblk-1/E93, which functions downstream of ecdysone signaling during metamorphosis, targets genes involved in synaptic plasticity underlying memory and learning ability in the adult honey bee brain. On the other hand, the ecdysone receptor (EcR), which is expressed in small-type KCs in the MBs, was reported to target genes involved in lipid metabolism in the brain during foraging flight. The target genes for Mblk-1 and EcR in the adult brains differed from those during metamorphosis, implying that the reiterative use of some transcription factors involved in ecdysone signaling, such as EcR and Mblk-1, has contributed to the acquisition of novel MB functions in Aculeata species, including the honey bee.